Research on Rural Settlement Landscape Visualization and Participatory Planning Based on Virtual Reality and Augmented Reality Technology - Li, Haiyuan; Nie, Daogu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Rural settlement planning stands at the intersection of economic growth, environmental preservation, and stakeholder satisfaction, necessitating innovative approaches to inform well-balanced decisions. The paper presents an innovative approach to rural settlement landscape visualization and participatory planning through the integration of virtual reality (VR) and augmented reality (AR) technologies. Leveraging a novel probabilistic model based on Generative Adversarial Networks (GANs), the study explores various scenarios by simulating realistic landscapes that account for economic viability, environmental sustainability, and stakeholder satisfaction. The GAN-augmented virtual reality model allows stakeholders to immerse themselves in different scenarios, enhancing engagement and collaboration. The paper evaluates scenarios across diverse dimensions, offering a comprehensive understanding of trade-offs and synergies. Findings underscore the significance of balanced land use distribution, population density, and economic impact. The integration of VR and AR technologies further fosters participatory planning, enabling stakeholders to visualize and comprehend diverse scenarios more effectively. This interdisciplinary approach bridges computer science, urban planning, and environmental sustainability, contributing to evidence-based decision-making and resilient rural development. The paper’s methodologies and insights equip urban planners, policymakers, and researchers with valuable tools for crafting sustainable rural communities.